The Impact of Beauty Product Reviews by Androgyny Influencer on Generation Z - Christian Haposan Pangaribuan, Jessica Claudia Audina, Desman Hidayat, Okta Prihatma Bayu Putra (International Journal of Advanced Science and Technology, 2020)
Even though social media influencers are thriving over the Internet, a representation of androgyny beauty influencer is still seen in most cultures and societies as unacceptable. The purpose of this study is to offer a comprehensive reflection on influencer marketing opportunities by an androgyny and determine the impact on consumer behavior of Generation Z. To test the proposed research model, we collected primary data using a questionnaire survey from 171 online shoppers in the capital city of Jakarta (Indonesia) and its vicinity. A multiple regression model was used to ascertain the significance of certain predictors of purchase intention and behavior. The research findings confirm that the influencer’s attractiveness is the only factor that influences the respondents’ attitudes and subjective norm on consumer behavior, which leads to different marketing opportunities. Keywords: TEARS Model, Androgyny, Beauty Influencer, Generation Z, Purchase Intention